Efficiency of 3,4- dihydropyrimidin -2 (1H) Derivative Compounds in Inhibition Fungi Associated with Wheat Seeds - Ahmed Ihsan Flayyih Al-Jawhari (Journal of Global Pharma Technology, 2018)
This  study  conducted  to  synthesis  and  identification  of  3,4 - dihydropyrimidin  -2 (1H)  derivative  compounds  , and  also  study  the  efficiency  of  these  compounds  in  inhibition    fungi  associated  with  wheat  seeds . The  results  showed  that  three  compounds  were  synthesis  and identificate  by  using  Infrared  spectroscopy  (IR)  ,  H-MMR and  Mass  spectroscopy .  The  result  showed  that  three  species  of  fungi  were  isolated  from  wheat  seeds  , these  fungi  were  Rhizoctoniasolani  ,  Trichodermalignorum  and  Aspergillusniger.  The  results  obtained   that  compound  ( 3a )  was  more  efficiency  to  inhibition  all  fungi  isolated  , and  the  statistical  methods  showed  no  significant  between  different  concentrationsof compounds . Keywords: Dihydropyrimidin, Monastrol, Fungi, Fungicides, Wheat, Seeds.